PEMERIKSAAN DINI GOLONGAN DARAH PADA SANTRI PONPES TAHFIDZIL QURAN AL-ASROR - M Shofwan Haris (STIKES NGUDIA HUSADA MADURA, 2019)
Blood is one of the most important components in the body, considering its function as a means of transportation. Lack of blood in the body can spur a number of diseases starting from anemia, hypotension, heart attacks, and several other diseases. Law number 36 of 2009 concerning health states that a health service facility is a tool and / or place used to carry out promotional, preventive, curative and rehabilitative health service efforts which are carried out by the government, local government and / or the community (Kemenkes RI , 2015). Based on a survey through interviews with students of SMKN 2 Bangkalan that had been conducted, it was found that many students at SMKN 2 Bangkalan still did not know their blood type. The method used to carry out community service is by collecting data on the number of students at SMKN 2 Bangkalan, then conducting interviews with students about their blood group and then making a time contract with the students. The activity was continued with a blood group examination for santri santri who did not know their blood type. The participants of the activity were 37 students at SMKN 2 Bangkalan who took part in the blood group examination. While participating in the activities, the students were very enthusiastic about the activities being carried out. The results of the activities most of the gender of the students were male as many as 21 people (56.8%). And, most of the students' blood groups were O as many as 13 people (35.2%)